Management of Islamic Boarding School Education Units in the Era of Collaborative Financing at the Raudlatul Mutaallim Islamic Boarding School, Tasikmalaya City - Yusuf; Evi Hanafiah; Hilya Anisa Sholihat Islamy; Dwi Rahayuningsih (al-Afkar, Journal For Islamic Studies, 2024)
This study describes the management of pesantren education units in the era of collaborative financing at raudlatul mutaallim boarding school in Tasikmalaya City. Most of the boarding schools in Indonesia use their own funds to meet their educational needs. Moreover, salafiyah pesantren that do not have formal education institutions in it, so they do not get operational funds from the government, so salafiyah pesantren must independently meet their own needs, starting from finding sources of funds, managing funds, to monitoring and evaluating the funds used. Because Pesantren Raudlatul Mutaallim Tasikmalaya City is a salafiyah-based pesantren and does not get funds from the government, so Pesantren Raudlatul Mutaallim Tasikmalaya City independently seeks sources of funds for the management of the pesantren. The purpose of this research is to find out where the sources of funding come from at the Raudlatul Mutaallim Islamic Boarding School in Tasikmalaya City and to find out what the allocation of funds and budget planning are for. This research uses a qualitative approach by using observation, interviews, and documentation as data collection techniques. The results of this study indicate that the financing of education at the Raudlatul Mutaallim Islamic Boarding School in Tasikmalaya City every year has increased, and the increase is adjusted to the implication or basic food ingredients which every year experience a decrease in the budget.